Answer:
steps 2 and 3 must be switched
Step-by-step explanation:
e2020
Answer:
![(x-7)^2+(y-2)^2=34](https://tex.z-dn.net/?f=%28x-7%29%5E2%2B%28y-2%29%5E2%3D34)
Step-by-step explanation:
We want to find the equation of a circle with a center at (7, 2) and a point on the circle at (2, 5).
First, recall that the equation of a circle is given by:
![(x-h)^2+(y-k)^2=r^2](https://tex.z-dn.net/?f=%28x-h%29%5E2%2B%28y-k%29%5E2%3Dr%5E2)
Where (<em>h, k</em>) is the center and <em>r</em> is the radius.
Since our center is at (7, 2), <em>h</em> = 7 and <em>k</em> = 2. Substitute:
![(x-7)^2+(y-2)^2=r^2](https://tex.z-dn.net/?f=%28x-7%29%5E2%2B%28y-2%29%5E2%3Dr%5E2)
Next, the since a point on the circle is (2, 5), <em>y</em> = 5 when <em>x</em> = 2. Substitute:
![(2-7)^2+(5-2)^2=r^2](https://tex.z-dn.net/?f=%282-7%29%5E2%2B%285-2%29%5E2%3Dr%5E2)
Solve for <em>r: </em>
<em />
<em />
Simplify. Thus:
![25+9=r^2](https://tex.z-dn.net/?f=25%2B9%3Dr%5E2)
Finally, add:
![r^2=34](https://tex.z-dn.net/?f=r%5E2%3D34)
We don't need to take the square root of both sides, as we will have the square it again anyways.
Therefore, our equation is:
![(x-7)^2+(y-2)^2=34](https://tex.z-dn.net/?f=%28x-7%29%5E2%2B%28y-2%29%5E2%3D34)
Answer:
HL
Step-by-step explanation:
36 inches because 12,24,36 and 18,36, 36=36